Addressing the need for forensic psychological evaluations of asylum seekers: The potential role of the general practitioner. (February 2020) - Singer, Elizabeth; Eswarappa, Meghana; Kaur, Khushmit; Baranowski, Kim A.
Highlights: Asylum seekers who have survived torture may experience a wide range of psychological symptoms associated with depression, anxiety, and posttraumatic stress disorder. The need for forensic psychological evaluations exceeds the number of mental health clinicians available to provide these assessments. Primary care physicians, professionals who already play essential roles in the identification and treatment of mental health issues, may be able to conduct these evaluations. This study found that non-mental health practitioners with experience in psychological forensic evaluations reached a level of confidence in conducting evaluations of asylum seekers comparable to general mental health practitioners. This study highlights areas of opportunity for curriculum development for general practitioners of all skill levels. Abstract: Asylum seekers who have survived torture and other abuses may experience a wide range of psychological symptoms associated with depression, anxiety, and posttraumatic stress disorder. During the asylum process, attorneys might refer their clients to clinicians who document these psychological sequelae of human rights violations. However, the need for forensic psychological evaluations exceeds the number of mental health clinicians available to provide these assessments. It has been suggested that primary care physicians, professionals who already play essential roles in the identification and treatment of mental health issues, may be able to conduct these evaluations. Yet, there is little empirical knowledge of what prior training and clinical experiences support mental health and non-mental health professionals who engage in this work, and what is needed to prepare general practitioners to provide forensic psychological evaluations to asylum seekers. This pilot study found non-mental health practitioners with experience in psychological forensic evaluations reached a level of confidence in conducting evaluations of asylum seekers comparable to general mental health practitioners. The study also identified clinicians' perceptions of training that supports them in their forensic psychological evaluations, their professional development needs, and the potential for general practitioners to leverage their current skill sets in this work.